I wanna iguana - Orloff, Karen Kaufman; Catrow, David (New York : G.P. Putnam's Sons, 2004)
Alex and his mother write notes back and forth in which Alex tries to persuade her to let him have a baby iguana for a pet.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Keywords: Iguanas as pets -- Fiction; Pets -- Fiction; Letters -- Fiction; Mothers and sons -- Fiction; Iguanas as pets -- Juvenile fiction; Pets -- Juvenile fiction; Letters -- Juvenile fiction; Mothers and sons -- Juvenile fiction